2016
DOI: 10.1159/000449232
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure of Male Slings and Artificial Urinary Sphincters: Results from a Large Middle European Cohort Study

Abstract: Introduction: We analysed the impact of predefined risk factors: age, diabetes, history of pelvic irradiation, prior surgery for stress urinary incontinence (SUI), prior urethral stricture, additional procedure during SUI surgery, duration of incontinence, ASA-classification and cause for incontinence on failure and complications in male SUI surgery. Materials and Methods: We retrospectively identified 506 patients with an artificial urinary sphincter (AUS) and 513 patients with a male sling (MS) in a multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
3
27
1
Order By: Relevance
“…Peri-and postoperative complications generally are rare in MS [19] and this also applies to this study. For instance, Leruth et al [20] reported sling infections in 1.7% in a cohort of 173 patients and Bauer et al [21] in 0.8% out of 124 patients.…”
Section: Discussionsupporting
confidence: 55%
“…Peri-and postoperative complications generally are rare in MS [19] and this also applies to this study. For instance, Leruth et al [20] reported sling infections in 1.7% in a cohort of 173 patients and Bauer et al [21] in 0.8% out of 124 patients.…”
Section: Discussionsupporting
confidence: 55%
“…Very few data are available on the correlation of anticoagulation therapy and AUS outcomes. A recent study conducted on 506 patients demonstrated that DM was associated with a higher incidence of impaired wound healing after AUS implant (7.3 vs 1.7%, P = 0.003), but no correlation to dry rate and revision rate was reported . Another cohort of AUS patients ( n = 954) showed that among diabetic patients, the incidence of infection and erosions at 5 years was higher compared to those without diabetes (13% vs 8%; P = 0.025); however, there was no difference between diabetic patients and controls in terms of social continence (45% vs 57%; P = 0.29) and subjective satisfaction (95% vs 90%; P = 0.43) …”
Section: Discussionmentioning
confidence: 98%
“…A recent study conducted on 506 patients demonstrated that DM was associated with a higher incidence of impaired wound healing after AUS implant (7.3 vs 1.7%, P = 0.003), but no correlation to dry rate and revision rate was reported. 42 Another cohort of AUS patients (n = 954) showed that among diabetic patients, the incidence of infection and erosions at 5 years was higher compared to those without diabetes (13% vs 8%; P = 0.025); however, there was no difference between diabetic patients and controls in terms of social continence (45% vs 57%; P = 0.29) and subjective satisfaction (95% vs 90%; P = 0.43). 41 Our overall and specific complication rate is in line with a recently published review on AUS safety: infection rate ranged from 0.5% to 10.6%, erosion rate ranged from 2.9% to 12%, urethral atrophy rates ranged from 1.6% to 11.4%, mechanical failure rates ranged between 5% and 29%.…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence to consider that AUS placement is superior to a secondary transobturator male sling after primary sling failure [19], but randomized trials for this specific indication are lacking. On the other hand, recurrent or persistent SUI after AUS may result from different scenarios leading to explant in 1 out of 5 devices in the short term [20]. Urethral erosion requires explantation of the 3 components due to potential bacterial colonization of the cuff.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the light of our results, we prove the concept that ATOMS implant after failed male sling or failed AUS is feasible and could be a reasonable alternative, especially in patients with former urethral reconstruction due to sling or AUS erosion. The low risk of urethral erosion and other postoperative complications [14,20] favor the choice of ATOMS, as it may be subject to less mechanical failures and need of revision surgery. Ultimately, the decision must be individualized and made taking into consideration the patient's expectations and the risks of further complications.…”
Section: Discussionmentioning
confidence: 99%